Optimation of Green Synthesis Biopolymer Cellulose Using Acetobacter xylinum From Whey as Media of Bacteria - Suharni Sinaga; Junius Gian Ginting; Helen Anjelina Simanjuntak; Dame Meldaria sipahutar; Defacto Firmawai Zega; Yanti Yanti; Sahat Sinaga; Lydia Barus; Hermawan Purba (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2023)
Utilizing waste into a more valuable commodity was one of the objectives of that research. Waste which initially became an environmental pollutant factor could be processed into more useful products. Tofu liquid waste was referred to whey was a by-product of tofu production. Whey was waste that still contains organic materials such as protein, fat, carbohydrates and minerals. That whey was used as a growth medium for Acetobacter xylinum bacteria and produces cellulose biopolymer as a result of carbohydrate fermentation. The process of optimizing carbohydrate fermentation by Acetobacter xylinum bacteria was carried out by varying the ratio of the amount of whey to coconut water, the acidity level of the media, and the fermentation time. The research results showed that the biosynthesis of cellulose biopolymer was obtained from a ratio of whey concentration to coconut water of 1:1, variations in acidity levels showed that the optimum fermentation conditions occurred at pH 4, and the optimal amount of cellulose biopolymer was obtained on day 21, namely with the highest percent yield value. The resulting biocellulose was characterized using FTIR, XRD, and SEM. The characterization results show that biocellulose is well formed with a fiber surface shape and particle size in the range of 50-200 nm